2012
DOI: 10.5194/hess-16-1-2012
|View full text |Cite
|
Sign up to set email alerts
|

A multi-source satellite data approach for modelling Lake Turkana water level: calibration and validation using satellite altimetry data

Abstract: Abstract. Lake Turkana is one of the largest desert lakes in the world and is characterized by high degrees of interand intra-annual fluctuations. The hydrology and water balance of this lake have not been well understood due to its remote location and unavailability of reliable ground truth datasets. Managing surface water resources is a great challenge in areas where in-situ data are either limited or unavailable. In this study, multi-source satellite-driven data such as satellite-based rainfall estimates, m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 66 publications
1
74
0
Order By: Relevance
“…Ideally, satellite-based precipitation data require a local calibration, as mentioned in Section 3.1.1, but without rain gauges installed over water surfaces, it is impossible to conduct a decent calibration. The original satellite precipitation data have been used to quantify precipitation over the lake in many studies, e.g., [2,51] for Lake Victoria and [52] for Lake Turkana. In this study, none of the available 20 rain gauge stations are located over the lake surface, and only five stations are located relatively near the shoreline (Figure 1).…”
Section: Precipitation Over the Lake (P Lake )mentioning
confidence: 99%
“…Ideally, satellite-based precipitation data require a local calibration, as mentioned in Section 3.1.1, but without rain gauges installed over water surfaces, it is impossible to conduct a decent calibration. The original satellite precipitation data have been used to quantify precipitation over the lake in many studies, e.g., [2,51] for Lake Victoria and [52] for Lake Turkana. In this study, none of the available 20 rain gauge stations are located over the lake surface, and only five stations are located relatively near the shoreline (Figure 1).…”
Section: Precipitation Over the Lake (P Lake )mentioning
confidence: 99%
“…Validation studies of RFE over the Ethiopian highlands using gauge data suggested that RFE can be reliably used for early warning systems to empower the decision making process (Dinku et al, 2008;Beyene and Meissner, 2010). Reliable use of RFE data to model Lake Turkana water levels with reasonable accuracy was demonstrated by Velpuri et al (2012). RFE data from January 1998 to December 2009 are used in this study.…”
Section: Data Usedmentioning
confidence: 99%
“…In this paper we use the lake level modeling approach presented by Velpuri et al (2012). This approach uses a multisensor multi-source approach to monitor lake water levels by integrating digital elevation data, satellite-based rainfall estimates, modeled ET, runoff data, and other satellite products.…”
Section: Lake Level Modeling Approachmentioning
confidence: 99%
“…The Omo basin is part of the large Turkana system with a catchment area of 131,000-145,500 km 2 covering southwestern Ethiopia and northern Kenya (Feibel 2011;Velpuri et al 2012). The Turkana system essentially consists of the Omo-Gibe (or simply, Omo) River and Lake Turkana.…”
Section: Study Sitesmentioning
confidence: 99%
“…One of these, the Omo-Turkana basin, spans a large part of the southwestern Ethiopian highlands and northern Kenya (Feibel 2011;Velpuri et al 2012) (Figure 1). …”
Section: Introductionmentioning
confidence: 99%